The role of worked-example in enhancing students’ self-explanation and cognitive efficiency in calculus instruction - Cecep Anwar Hadi Firdos Santosa; Didi Suryadi; Sufyani Prabawanto; Syamsuri Syamsuri (Jurnal Riset Pendidikan Matematika, 2018)
This research was aimed to investigate the effect of students’ self-explanation to their achievement, mental effort, and cognitive efficiency while studying mathematics, particularly in integral topics. This research used a static-group comparison design implemented to first-year undergraduate students. The subject of the study consists of 64 first year undergraduate students in one of the universities in Banten province, Indonesia. The students were divided into two classrooms, experimental and control. Experimental classroom received worked-example method whereas control classroom studying without worked-example method. Instruments used in this research include achievement tests, rating scale mental effort, deviation model of cognitive efficiency, and teaching materials in the form of worked-example. The results show that the implementation of self-explanation through worked-example helps students get a higher achievement, lower mental effort, and better cognitive efficiency compared to students who get instruction without worked-example method. The research also reveals the important role of worked-example in enhancing the ability of students’ self-explanation.